Volume 1: Fora, Parts a and B 2002
DOI: 10.1115/fedsm2002-31398
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling and Experimental Characterization of Indoor Aerosol Transport

Abstract: When a hazardous aerosol or gas is inadvertently or deliberately released in an occupied facility, the airborne material presents a hazard to people. Inadvertent accidents and exposures continue to occur in Los Alamos and other nuclear facilities despite state-of-art engineering and administrative controls, and heightened diligence. Despite the obvious need in occupational settings and for homeland defense, the body of research in hazardous aerosol dispersion and control in large, complex, ventilated enclosure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Dispersion of aerosols in large room was found to be advection-dominated as opposed to diffusiondominated (Konecni et al 2002). This shortcoming results due to the lack of coupling of aerosol dynamics with CFD framework.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Dispersion of aerosols in large room was found to be advection-dominated as opposed to diffusiondominated (Konecni et al 2002). This shortcoming results due to the lack of coupling of aerosol dynamics with CFD framework.…”
Section: Introductionmentioning
confidence: 93%
“…Haim et al (2000) showed that the computer simulation to estimate the air ow patterns in nuclear workplace can be very useful in decision making of the appropriate location of air samplers. Konecni et al (2000) in their study using computational uid dynamics (CFD) indicated that a strategy based on quantitative parameters are superior to the more traditional strategy of placing CAMs in front of potential release points or near to the exhaust points. In their study of a granite processing plant (Dieguez-Elizondo et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation